Survival Benefit of Surgical Resection for Pancreatic Neuroendocrine Tumors With Oligometastatic Liver Metastasis: A Retrospective and Propensity Score-Matching Analysis - Yang, Zhen; Liang, Jie; Leng, Kaiming; Shi, Guangjun (Frontiers in Oncology, 2022)
Abstract Background: Pancreatic neuroendocrine tumors (PanNETs) are a heterogeneous group of pancreatic malignancies. Surgical resection is the only curative treatment option for patients with localized PanNETs, yet the role of cancer directed surgery (CDS) in the setting of oligometastatic liver metastasis remains controversy. Methods: All patients diagnosed with PanNETs and liver-only metastasis from 2010 to 2018 were identified from the SEER database. The biases of baseline characteristics between CDS and no-CDS cohorts was reduced by propensity score matching (PSM) method, and the prognostic role of CDS was estimated using Kaplan-Meier method and Cox regression models. Logistic regression analysis was utilized to identify factors associated with patients who underwent CDS. Results: A total of 1270 PanNETs patients with oligometastatic liver metastasis were included and analyzed. Of these patients, 283 (22.3%) patients underwent CDS of the primary tumor, while the remaining 987 (77.7%) did not. The OS and CSS were significantly better in the CDS cohort regardless of the propensity score analysis. Multivariate analysis revealed that age, tumor differentiation, tumor location, and lymph node status were significantly associated with patients who were more likely to receive CDS. Conclusion: Our study demonstrated that CDS was associated with survival benefit in selected patients with PanNETs and liver-only metastasis based on a large population database.